Anti-PD-1 checkpoint blockade monotherapy in the orthotopic GL261 glioma model: the devil is in the detail. Issue 1 (14th May 2021) - Tritz, Zachariah P; Ayasoufi, Katayoun; Johnson, Aaron J
Abstract: The GL261 cell line, syngeneic on the C57BL/6 background, has, since its establishment half a century ago in 1970, become the most commonly used immunocompetent murine model of glioblastoma. As immunotherapy has entered the mainstream of clinical discourse in the past decade, this model has proved its worth as a formidable opponent against various immunotherapeutic combinations. Although advances in surgical, radiological, and chemotherapeutic interventions have extended mean glioblastoma patient survival by several months, 5-year survival postdiagnosis remains below 5%. Immunotherapeutic interventions, such as the ones explored in the murine GL261 model, may prove beneficial for patients with glioblastoma. However, even common immunotherapeutic interventions in the GL261 model still have unclear efficacy, with wildly discrepant conclusions being made in the literature regarding this topic. Here, we focus on anti-PD-1 checkpoint blockade monotherapy as an example of this pattern. We contend that a fine-grained analysis of how biological variables (age, sex, tumor location, etc.) predict treatment responsiveness in this preclinical model will better enable researchers to identify glioblastoma patients most likely to benefit from checkpoint blockade immunotherapy moving forward.